2004
DOI: 10.1111/j.0001-6349.2004.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress urinary incontinence 4 years after the first delivery: a retrospective cohort survey

Abstract: Our results suggest that stress urinary incontinence after pregnancy arises from a multifactorial condition. The main risk factors are: age, previous incontinence (before or during the first pregnancy), prolonged labor and vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 37 publications
3
44
0
8
Order By: Relevance
“…Fritel et al, in their study showed that cesarean was significantly associated with a lower risk of SUI compared to normal delivery. 24 It is not known whether by increasing the number of caesarean sections, the incidence of SUI could be decreased. Even reverse can be considered true that, women requiring cesarean have more inflexible connective tissue (lower incidence of SUI), leading to delayed cervical dilatation, requiring surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Fritel et al, in their study showed that cesarean was significantly associated with a lower risk of SUI compared to normal delivery. 24 It is not known whether by increasing the number of caesarean sections, the incidence of SUI could be decreased. Even reverse can be considered true that, women requiring cesarean have more inflexible connective tissue (lower incidence of SUI), leading to delayed cervical dilatation, requiring surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…5 Epidemiological studies indicate that risk factors for UI are age, parity, previous pelvic or perineal surgery, obesity and chronic diseases. [6][7][8][9][10][11] More recently, a report that major depression may be involved in the onset of UI has opened up the field to new pathophysiological hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is questionable whether cesarean section delivery can prevent pelvic floor injury, [3][4][5] but recent data have suggested that this protective effect is less pronounced and that gestational urinary incontinence appears to be the most important predictive factor for developing postnatal urinary incontinence. [6][7][8] The risk of urinary incontinence has been found to be higher among women who had only experienced cesarean delivery than among nulliparous women, and even higher among those who had only delivered vaginally. 9 In women without urinary incontinence, the pelvic floor muscles contract simultaneously with or immediately before increases in abdominal pressure as an unconscious involuntary automatic co-contraction.…”
Section: Introductionmentioning
confidence: 99%